Emotional Resilience and Mindfulness in Educators: Insights into Stress, Well-Being, and Perceived Training Needs - Munggarani, Febi; Nurhayati, Sri; Taufikin, Taufikin (JURNAL DIMENSI, 2025)
Teaching is widely recognized as a high-stress profession, significantly impacting educators' well-being and professional performance. This study explores the relationship between stress, mindfulness, and emotional resilience among educators, with a focus on readiness for emotional management training. Using a quantitative methodology, the research collected data from 30 educators in Cimahi, Indonesia, employing structured questionnaires to measure stress levels, mindfulness awareness, emotional challenges, and training readiness, establishing a clear baseline for intervention. The findings highlight pervasive stress levels, mainly attributed to workload and classroom pressures, negatively affecting teaching quality and relationships. Foundational mindfulness skills were evident, yet significant gaps in emotional regulation, particularly in managing impulsive reactions, persisted. Importantly, educators displayed high readiness for emotional management training, especially those under greater stress, underscoring the potential for targeted, impactful professional development. The interplay between stress, mindfulness, and readiness for training points to the need for holistic, integrated interventions. This research advances the understanding of educator well-being by bridging local insights with global evidence. It advocates systemic reforms to alleviate workload and improve access to emotional support resources.